Structure of the Mesozoic rocks in the Kuqa Basin (NW China) - Xiang Li; Ruth Soto; Hou Guiting (Geogaceta)
The deformation of sub- and supra-salt structures in the Kuqa Basin exhibits a clear decoupling relationship. Difficulty in identifying deep structures below the Eocene regional detachment level has led to controversy over Cenozoic deformation affecting Mesozoic rocks and Mesozoic deformation itself. This work aims to revise and compile published data (geological and geophysical data and detrital zircon U-Pb ages) to understand the structure affecting the Mesozoic rocks of the Kuqa Basin. The results indicate significant Mesozoic basement-involved structures which were subsequently modified by Cenozoic compressional tectonics. Further investigation of this phenomenon is critical for understanding the overall tectonic evolution of the Kuqa Basin.